The persuasiveness of different sources of information on the decision to vaccinate. A cross-sectional study in Germany during the pandemic at the turn of the year 2021/2022 - Susanne Jordan; Sarah Jane Böttger; Sabine Zinn (PLoS ONE, 2025)
Health information about vaccinations is communicated via various sources of information and is crucial for vaccination decisions. Information sources such as interpersonal sources, traditional print and digital media as well as social media offer information about the risks and benefits of vaccination. During health crises such as the COVID-19 pandemic was, some information sources provide hanging or contradictory information, alongside with misinformation and disinformation. Little is known about the relationship between the reported persuasiveness of different sources of information for individual vaccination decisions and differences in this between the vaccinated and unvaccinated. Utilizing data from 10,284 participants in the “Corona-Monitoring Nationwide” survey in Germany from winter 2021/22, this study explored the relationship between the persuasiveness of information sources and vaccination decisions, considering socio-demographic and pandemic-related factors. For more than half of respondents, talks with family, friends, and acquaintances were the most convincing. Traditional media like television and radio were reported by 44%. Newspapers/magazines (online or print) and talks with physicians were each found the most convincing by around one third. About one fifth were persuaded by public authority’s flyers or websites. Less than a tenth each was convinced by social media/messenger services, brochures from pharmacies and health insurances, talks with pharmacy staff or online health portals. Significant differences emerged between vaccinated and unvaccinated individuals. Unvaccinated people were four times more likely to report social media and messenger services as convincing compared to vaccinated people. Reporting talks with doctors and flyers/websites from public authorities as very persuasive significantly reduced the likelihood of being unvaccinated. The findings suggest that in future health crises, information should be disseminated through diverse sources, using both traditional and digital media, as well as interpersonal communication. Proactive science communication on social media and messenger services is crucial to counteract misinformation and disinformation.